THE INFLUENCE OF A GUIDED INQUIRY LEARNING MODEL IN IMPROVING STUDENTS' CREATIVE THINKING ABILITIES: A META-ANALYSIS STUDY - I Made Elia Cahaya; Ni Made Ayu Suryaningsih; I Made Yoga Parwata; Christiani Endah Poerwati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
Critical thinking skills are necessary in everyday life and are the main competencies that students must have in the 21st century which is full of competition. The guided inquiry learning model improves students' creative thinking skills and is able to bridge the theory obtained at school with the real world in society. This research is a meta-analysis research aimed at analysing the influence of the guided inquiry learning model in improving students' creative thinking abilities. Data was obtained from searching scientific articles published in accredited journals Science and Technology Index (SINTA). Articles published from 2016 to 2022. The research sample that met the inclusion and exclusion criteria was 7 articles. Data were analysed using the JASP V. 0.11 software application. Heterogeneity test results showed Q value = 63.426 and p value < 0.001. Model combining effect size used random effect model. The research results showed a combined effect size value of 1.10 with a very high effect category and Fail-safe test results N> 5k + 10, indicating there was no publication bias. The results of this meta-analysis research contributed to strengthening the findings of previous research.